Planteamiento de una metodología que permita calcular el deterioro del valor de los activos fijos de conformidad con lo establecido en la NIC 36 a partir de la convergencia contable colombiana (2012)
This degree work aims to raise a methodology that allows to calculate the deterioration of the value of the assets in accordance with the Standard International Accounting IAS 36, having as main priority accounting convergence that the Colombian nation experiences by mandate of the 2009 Act 1314, which regulates the principles and standards of accounting and financial reporting and assurance of information accepted in Colombia with the goal of converging with the accounting standards issued by the Council of international standards of accounting (IASB), identifying the theory and the procedure for the calculation of the deterioration of the value of the assets in execution of documents exposed by this agency, also recognizing those procedures submitted by Argentina, Chile and Mexico to determine the impairment of the asset, for this reason we study different forms of as a country implements the IAS/IFRS in accordance with the accounting regulatory bodies existing in each territory, as final conclusion suggests an appropriate procedure for the calculation of the deterioration of the value of the assets in a convergence between the rules set out by the IASB and the principles of accounting generally accepted (GAAP) in Colombia, to the end, that its use is feasible at the time to implement international accounting standards.